DERIVATIONS OF TENSOR PRODUCT OF SIMPLE C*-ALGEBRAS (Journal of Sciences, Islamic Republic of Iran)
In this paper we study the properties of derivations of A B, where A and B are simple separable C*-algebras, and A B is the C*-completion of A B with respect to a C*-norm Yon A B and we will characterize the derivations of A B in terms of the derivations of A and B